1975
DOI: 10.1111/j.1365-246x.1975.tb06195.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Pseudotachylyte by Ancient Seismic Faulting

Abstract: Pseudotachylyte occurs as vein material infilling highly brittle shear and extensional fractures developed along the western margin of the late Caledonian, Outer Hebrides Thrust zone in NW Scotland. Vein geometries and textures show clearly that the pseudotachylyte has been through a melt phase. From the composition of the pseudotachylyte matrix which is close to that of a basaltic andesite, probable melt temperatures of around 1100 "C are inferred. Field and theoretical studies demonstrate that the pseudotach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
559
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 740 publications
(581 citation statements)
references
References 29 publications
22
559
0
Order By: Relevance
“…Field and laboratory studies have shown that pseudotachylites produced by frictional melting contribute to co-seismic weakening (Sibson, 1975;Goldsby and Tullis, 2002;Di Toro et al, 2004). The occurrence of glass textures in TCDP samples from Holes A and B clearly shows that frictional melting occurred.…”
Section: Amorphous Material/meltingmentioning
confidence: 96%
“…Field and laboratory studies have shown that pseudotachylites produced by frictional melting contribute to co-seismic weakening (Sibson, 1975;Goldsby and Tullis, 2002;Di Toro et al, 2004). The occurrence of glass textures in TCDP samples from Holes A and B clearly shows that frictional melting occurred.…”
Section: Amorphous Material/meltingmentioning
confidence: 96%
“…The minimum depth estimate of 2.2 + 1.0 km lies near the upper bound of the 1-15 km-depth range considered most appropriate for the generation of pseudotachylite by seismic faulting (Sibson 1975(Sibson , 1977. Certainly, the corrected age, even as a minimum value, is more in accord with the recent uplift history across the Alpine Fault than the K-Ar wholerock age of9.8 Ma obtained by Adams (1981) from a pseudotachylite vein in Harold Creek, 120 km along the fault zone to the northeast.…”
Section: Discussionmentioning
confidence: 79%
“…It has been suggested that pseudotachylites are the product of ultracomminution rather than fusion (Wenk 1978), but there is often good textural evidence for the former existence of a melt phase (Park 1961;Sibson 1975;Maddock 1983). In the Alpine Fault material, transmission electron miscroscopy (TEM) has revealed some surviving patches of glass, though devitrification to a chlorite-rich groundmass is generally well advanced (Sibson et al 1979; see also Wallace 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Pseudotachylite is thought by most to be the definitive record of 43 an earthquake where dynamic strength was controlled by shear melting [Jeffreys, 1942;44 McKenzie and Brune, 1972;Sibson, 1975] as we have assumed, and if the apparent stress,  a , is relatively small. For shear melting there are 156 no published proportions of radiated energy and heat from laboratory measurements.…”
Section: Field Observations and Melt Shear Strengthmentioning
confidence: 88%
“…A well-understood exception are the ancient earthquakes recorded in exhumed 42 pseudotachylites [Sibson, 1975]. Pseudotachylite is thought by most to be the definitive record of 43 an earthquake where dynamic strength was controlled by shear melting [Jeffreys, 1942;44 McKenzie and Brune, 1972;Sibson, 1975] as we have assumed, and if the apparent stress,  a , is relatively small.…”
Section: Field Observations and Melt Shear Strengthmentioning
confidence: 90%